Ethical Decision-Making in Educational Leadership: Insights from Islamic Scholars - Agus Setiawan (Edu Spectrum: Journal of Multidimensional Education, 2024)
Ethical decision-making in educational leadership is a critical aspect of ensuring effective governance and fostering a positive school climate. Insights drawn from Islamic scholars provide valuable perspectives on moral principles that guide leaders in educational settings. This study explores the ethical considerations and decision-making processes influenced by Islamic teachings among educational leaders. This research aims to investigate how Islamic scholars' insights inform ethical decision-making practices in educational leadership. It seeks to analyze the ethical frameworks advocated by Islamic teachings and their application in contemporary educational contexts. This study employs a literature review approach to examine scholarly articles, books, and Islamic texts that discuss ethical principles relevant to educational leadership. The research focuses on synthesizing and analyzing existing literature to identify key themes, principles, and practices advocated by Islamic scholars in guiding ethical decision-making among school leaders. The findings highlight that Islamic scholars emphasize principles such as justice (adl), compassion (rahma), honesty (sidq), and accountability (mas'uliyyah) as foundational to ethical leadership in education. Ethical decision-making processes are guided by Islamic teachings that prioritize the well-being of stakeholders, fairness in decision outcomes, and adherence to ethical norms. Insights from Islamic scholars offer nuanced perspectives that enrich contemporary discussions on ethical leadership and governance in educational settings